2009
DOI: 10.1097/mpg.0b013e318175ca7f
|View full text |Cite
|
Sign up to set email alerts
|

Growth Abnormalities Persist in Newly Diagnosed Children With Crohn Disease Despite Current Treatment Paradigms

Abstract: Growth delay persists in many children with CD following diagnosis, despite improved disease activity and the frequent use of immunomodulators and biologics. Additional strategies to improve growth outcomes require development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 27 publications
12
102
2
1
Order By: Relevance
“…However, growth delays often persist after diagnosis despite improvement in inflammatory biomarkers and treatment with biologic agents. 8,9 Therefore, failure to control inflammation puts this population at increased risk for fracture. The International Society for Clinical Densitometry recommends that children with IBD undergo a total body (excluding the skull) dualenergy radiograph absorptiometry (DXA) screen at diagnosis and at 6-month intervals if abnormalities are found.…”
Section: Growthmentioning
confidence: 99%
“…However, growth delays often persist after diagnosis despite improvement in inflammatory biomarkers and treatment with biologic agents. 8,9 Therefore, failure to control inflammation puts this population at increased risk for fracture. The International Society for Clinical Densitometry recommends that children with IBD undergo a total body (excluding the skull) dualenergy radiograph absorptiometry (DXA) screen at diagnosis and at 6-month intervals if abnormalities are found.…”
Section: Growthmentioning
confidence: 99%
“…Typowe objawy, takie jak: bóle brzucha, wzdęcia, biegunki z krwawieniem lub bez (jawnym bądź utajonym), ubytek masy ciała, mogą pojawić się jednocześnie lub po pewnym czasie trwania choroby. Unikalnym problemem w porównaniu z dorosłymi, który wymaga szczególnej uwagi u pacjentów w wieku rozwojowym, jest zahamowanie wzrostu i opóźnienie dojrzewania płciowego [10,11]. Na obraz kliniczny choroby wpływa nie tylko lokalizacja czy charakter zmian zapalnych, ale także aktywność stanu zapalnego.…”
Section: Wstępunclassified
“…In contrast, Sinitsky et al [121] reported a significant improvement in BMI z-score at one year of treatment with IFX in children with CD but failed to show significant changes in height velocity. Pfefferkorn et al [4] did find an improvement in height velocity z-scores during the first two years following diagnosis of CD though no difference between therapy regimens was noted. This discrepancy could be attributed to a relatively advanced pubertal stage in the first study and to heterogeneity in therapeutic regimens in the second one.…”
Section: Biologic Treatmentmentioning
confidence: 99%
“…Anti-TNF agents have a promising potential for improving growth as they were shown to induce prompt mucosal healing [110,111], reverse the pro-inflammatory cytokines cascade [113] and enable prolonged corticosteroid withdrawal [108][109][110]. Indeed, numerous studies suggest an increase in height velocity and height z-score following prolonged anti-TNF treatment, providing treatment is undertaken early enough prior to or during puberty [4,106,111,112,[114][115][116][117][118][119][120]. In contrast, Sinitsky et al [121] reported a significant improvement in BMI z-score at one year of treatment with IFX in children with CD but failed to show significant changes in height velocity.…”
Section: Biologic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation